Analisis Tren Mobillitas Sirkulretren mobilitas sirkuler, pandemi Covid-19 - Laela Nurul Istiqomah; Ika Afianita Suherningtyas, S.Si., M.Sc (Journal of Demography, Ethnography and Social Transformation, 2022)
The development of the Depok Sub-district, Sleman Regency is the impact of the overflow of activities originating from the city of Yogyakarta which causes an increase in urbanization and the growth of the surrounding area. The growth of the Depok District area is marked by the variety of educational, economic, and accessibility facilities that support mobility activities which are attracting factors for migrants to carry out circular mobility. Research on the Trend Analysis of Productive Age Circular Mobility in Depok District aims to determine the characteristics of migrants and mobility trends during the Covid-19 pandemic. The method used is descriptive quantitative analysis. The results showed that the mobility actors were 19-32 years old with the most mobility goals going to Caturtunggal. The trend of mobility during the pandemic is a decreasing trend in the frequency of daily mobility by 63.6%, and the frequency of 3-6 times a week 25%. The increase in mobility trends occurs at an intensity of 1-3 times a week by 71.4% and not doing mobility by 100%.